A yoga como instrumento de conscientização e conexão com a natureza - Delphino, Aline Monastero [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The practice of Yoga arose in India more than six thousand years ago. Initially it was transmitted orally. Involving physical, mental, emotional, spiritual, and social practices assists in positive behavioral constructs, being accessible to people of all ages, from children to older people. Its practice is motivating for the general public by providing the development of the human body, the evolution of the mind and strengthening ethical and moral principles always related to human nature. According to Patañjali, Yoga is the total directing of the senses and thoughts (mind) to a flow of stability. The present research aims to observe different areas of knowledge in the field of Physical Education and their possible relations and uses as instruments of awareness and education, making possible the use of resources related to the natural environment. As a method, it was decided to make an integrative review regarding the practices of Yoga and its relation with nature, as well as to bring some of the history of environmental education and its problems. It will also be presented some little known practices that associated can help in the awareness and education of environmental problems and preservation of the environment, besides showing the role of the physical education professional within this context

A prática de Yoga surgiu na Índia há mais de seis mil anos. Inicialmente ela era transmitida oralmente. Envolvendo práticas físicas, mentais, emocionais, espirituais e sociais, auxilia nas construções positivas do comportamento, sendo acessível a pessoas de todas as idades, desde crianças até pessoas mais velhas. Sua prática é motivadora para o público em geral por proporcionar o desenvolvimento do corpo humano, da evolução da mente e fortalecendo os princípios éticos e morais sempre relacionados à natureza humana. De acordo com Patañjali, Yoga é o direcionamento total dos sentidos e pensamentos (mente) a um fluxo de estabilidade. A presente pesquisa tem por objetivo observar diferentes áreas do conhecimento do campo da Educação Física e suas possíveis relações e utilizações como instrumentos de conscientização e educação viabilizando o uso de recursos relacionados ao ambiente natural. Como método decidiu-se fazer uma revisão integrativa a respeito das práticas de Yoga e de sua relação com a natureza, além de trazer um pouco do histórico da educação ambiental e suas problemáticas. Ainda serão apresentadas algumas práticas pouco conhecidas que associadas podem auxiliar na conscientização e educação de problemas ambientais e preservação do meio, além de mostrar o papel do profissional da educação física dentro deste contexto
Keywords: Ioga; Natureza; Educação fisica; Conscientização; Meio ambiente; Educação ambiental; Proteção ambiental